Gender Dynamics And Economic Empowerment Among Female Traders at The South Kalimantan Floating Market - Jumriani, Jumriani; Subiyakto, Bambang; Rusmaniah, Rusmaniah; Abbas, Ersis Warmansyah; Mutiani, Mutiani; Muhaimin, Muhammad; Ratković, Nada (LPPM Universitas PGRI Sumatera Barat, 2026)
This study examines the gender dynamics and economic Empowerment of female traders in the Floating Market of South Kalimantan, focusing on dual roles, adaptation strategies, and socio-economic support systems that develop among traders. Using a qualitative approach, this study involved in-depth interviews with female traders, observations, and documentation studies with various stakeholders. The results showed that female traders developed complex adaptive strategies in managing their dual roles, characterized by establishing an effective time management system and the involvement of family members in trading activities. Other important findings revealed that the informal financing system, primarily through arisan groups, is an effective support mechanism in economic Empowerment. The social networks formed not only act as an economic support system but also as a means of transferring knowledge and skills between generations. This study contributes to the understanding of the intersection of gender and economic Empowerment in the context of traditional markets while providing practical implications for the development of gender-responsive policies in community economic empowerment. The research findings recommend an integrated approach to the economic Empowerment of female traders that considers local socio-cultural aspects and the dual role of women in the family economy.